Influence of currents to temporal variation of brooder spawner corals recruitment density in Bidong Island, Malaysia - Rani, Husaini; Saad, Shahbudin; Ahmad, Zuhairi (2016)
Temporal variation of scleractinian coral recruitment density was examined at 3 sam-pling stations around Bidong Island, Malaysia in relation to currents speed in 2014. Although almost all corals were brooder spawners (Pocillopora, Stylopora and Seria-topora), the relationship between recruitment density and currents were differed among sampling stations, likely due to differences in coastal topography. Recruitment of brooder spawner corals varied between sampling stations, and recruitment was greater at leeward compared to windward reefs. This result suggests that embryonic develop-ment time and currents affect larval dispersal and subsequent recruitment patterns at a local scale. Based on embryonic development time, brooder spawner corals whose lar-vae develop more rapidly (internal fertilization) are likely to have higher rates of self-seeding than others. Our results predict that among spawning corals, local populations of brooder corals, whose larvae disperse short distances and recruit near to natal reef are not resilient to local disturbances, whose recruitment relies upon local stock com-pared to broadcast corals.